2005
DOI: 10.1143/jjap.44.7372
|View full text |Cite
|
Sign up to set email alerts
|

Electric and Crystallographic Characterizations on Hydrogen Passivated Spherical Silicon Solar Cells

Abstract: An approach towards quantum games is proposed that uses the unusual probabilities involved in EPR-type experiments directly in two-player games.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…As reported in previous studies, the diode ideality factor ( A ) is related to electron‐hole recombination in solar cells . As the A value is equal to one, the recombination in the neutral region dominates.…”
Section: Resultsmentioning
confidence: 78%
“…As reported in previous studies, the diode ideality factor ( A ) is related to electron‐hole recombination in solar cells . As the A value is equal to one, the recombination in the neutral region dominates.…”
Section: Resultsmentioning
confidence: 78%
“…Thus, the recombination at GBs could not be observed clearly. The EBIC contrast of the CIGS solar cell was low compared with that of polycrystalline Si solar cells, 11) where a clear EBIC contrast was observed in GBs and crystal grains. The results suggested that there was no significant difference in the number of effective recombination centers between GBs and crystal grains.…”
Section: Resultsmentioning
confidence: 85%
“…The properties of GBs in polycrystalline Si solar cells were often measured by the EBSD and EBIC techniques. [9][10][11][12][13][14][15] In CIGS films, EBSD measurements were performed mostly on the cross sections of CIGS films. [16][17][18][19][20][21] In ref.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[6][7][8][9][10][11][12] Flexible and light weight spherical Si solar cells are also anticipated, and will be valuable in situations such as responding to emergency disasters. The conversion ef ciencies of spherical Si solar cells can be increased by producing high-quality Si spheres, 3,4,[6][7][8][9][10][11][12][13][14][15] forming textured Si surface structures, 16) deactivating defects by passivation, 17) optimizing the concentrator module and re ector cup 18,19) and preparing anti-re ection (AR) lms on the spherical Si solar cells. 12,[20][21][22] Si spheres have typically been grown by a dropping method.…”
Section: Introductionmentioning
confidence: 99%